The ECB's half-baked supervision mandate Or, how to get serious about shadow banking again. Issue 3 (3rd July 2022) - Vestergaard, Jakob; Quorning, Stine
ABSTRACT: In debates on the need to "complete" the banking union, there has been little attention to the omission of shadow banks from the supervision mandate given to the European Central Bank with the establishment of the Single Supervisory Mechanism (SSM). We argue that there can be no completion of the banking union without dedicated pan-European supervision of all non-banking financial institutions. We identify four explanatory modalities for the omission of shadow banking from the SSM mandate and discuss organizational options for institutionalizing European supervision of its shadow banking sector.